60. The Biological Reserve of San Francisco (Ecuador): syntaxonomical and nomenclature vegetation revision - Izco, Jesús (Lazaroa, 2013)
After a revision of the syntaxonomy and nomenclature made by R.W. Bussmann of the vegetation of the Reserva Biológica San Francisco, Cordillera Oriental, in the south of Ecuador, new syntaxa and new names are proposed.